Photothermal and magnetic studies of Ni@Au nanotubes for anti-cancer therapies - Anton Anikin; Alena Shumskaya; Anna Motorzhina; Anastasia Gurevich; Sergey Bedin; Ilia Doludenko; Dinara Khairetdinova; Victor Belyaev; Kateryna Levada; Valeria Rodionova; Larissa Panina (Modern Electronic Materials)
Anisotropic ferromagnetic micro- and nanoparticles made of 3d metals demonstrate the ability to effectively influence micro- and nanoscale biological entities through hyperthermia and mechanical vibrations induced by magnetic fields. Multifunctional nanoparticles designed for combined therapies are particularly effective. This study explores the potential application of Ni@Au nanotubes to synergize magnetomechanical effects with photothermal heating. The orientation of nanotubes in a magnetic field was demonstrated by changes in the intensity of the light beam passing through a water suspension of nanotubes. The gold coating doubled the optical absorption of the solution in comparison with pure nickel nanotubes and resulted in the appearance of a resonance-enhanced peak in the range of 700–800 nm, the position of which is in accordance with theoretical calculations. The photothermal performance of nanotube solu-tions was quantitatively assessed by determining the photothermal conversion coefficient, which increased due to gold coating. However, it’s worth noting that the gold coating did not significantly reduce nanotube cytotoxicity in hepatocyte-derived cellular carcinoma cells (Huh7). The potential reasons for this outcome include the large particle size and non-uniform gold coating. Nevertheless, the combination of two anti-cancer therapies employing the same type of particles offers the opportunity to reduce particle concentration while maintaining the required therapeutic efficacy.